Application of Direct Instruction Learning Model to Improve Learning Outcomes of Electrical Power Installation - Renjaan, Johanis; Sagat, Kristianto; Atnangar, Micartur; Angmalisang, Harricoon (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2022)
This research is classroom action research that aims to analyze the application of the direct instruction learning model to improve the learning outcomes of Electrical Power Installation students of class XI SMK Siwa Lima St Yosep Langgur. This research was carried out in two cycles: planning, implementation, observation, and reflection stages. Data collection was done using tests and observations. Based on the research data analysis, the average value of students in the first cycle was 71.31, with a completeness percentage of 47.36%. In the second cycle, the students’ average score was 83.15, with a completeness percentage of 84.21%. From the results of this study, the conclusion that can be drawn is that the application of the direct instruction learning model can improve the learning outcomes of Electrical Power Installation students of class XI SMK Siwa Lima St Yosep Langgur.